2010
DOI: 10.1371/journal.pone.0014403
|View full text |Cite
|
Sign up to set email alerts
|

The Bacterial Intimins and Invasins: A Large and Novel Family of Secreted Proteins

Abstract: BackgroundGram-negative bacteria have developed a limited repertoire of solutions for secreting proteins from the cytoplasmic compartment to the exterior of the cell. Amongst the spectrum of secreted proteins are the intimins and invasins (the Int/Inv family; TC# 1.B.54) which are characterized by an N-terminal β-barrel domain and a C-terminal surface localized passenger domain. Despite the important role played by members of this family in diseases mediated by several species of the Enterobacteriaceae, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
84
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 57 publications
0
84
1
3
Order By: Relevance
“…This family, for which E. coli O157 intimin and Y. pseudotuberculosis invasin are archetypal, is now recognized in a number of Gramnegative organisms (31). The Ilp protein conforms to the general characteristics of this family, evidenced by an N-terminal signal sequence and N-terminal LysM domain, a highly conserved ␤-domain predicted to conform to a transmembrane ␤-barrel structure, and a C-terminal passenger domain localized on the cell surface.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This family, for which E. coli O157 intimin and Y. pseudotuberculosis invasin are archetypal, is now recognized in a number of Gramnegative organisms (31). The Ilp protein conforms to the general characteristics of this family, evidenced by an N-terminal signal sequence and N-terminal LysM domain, a highly conserved ␤-domain predicted to conform to a transmembrane ␤-barrel structure, and a C-terminal passenger domain localized on the cell surface.…”
Section: Discussionmentioning
confidence: 88%
“…The hmsHFRS and gmhS genes, encoding an extracellular polysaccharide and a modification of lipopolysaccharide core, respectively, are required for the formation of biofilm and blockage in the flea (7,13). Because several members of the intimin/invasin family of proteins have been implicated in biofilm formation (31) and because Ilp is expressed at lower temperatures, we investigated the potential role of Ilp on blockage and infectivity in the flea. Results showed that there were no differences in the blockage and infection rates by Y. pestis KIM6 ⌬ilp compared to those of the parental wild-type strain, suggesting that Ilp has a limited role, if any, in the transmission of Y. pestis from a flea to a mammalian host.…”
Section: Discussionmentioning
confidence: 99%
“…This domain can be found in peptidoglycan-degrading enzymes (autolysins) and is predicted to bind peptidoglycan (3,56). It might act as an additional base to stabilize the ␤-barrel autotransport structure of the large surfaceexposed portion of InvC (60). Alternatively, the LysM-type domain might be implicated in the translocation of the outer membrane protein through the cross-linked peptidoglycan layer (50).…”
Section: Discussionmentioning
confidence: 99%
“…This part of the protein is predicted to form a ␤-barrel structure in the outer membrane (OM), acting as an autotransporter of the surface-exposed C terminus. It is absolutely required for the secretion, assembly, and incorporation of the molecules into the OM and is necessary for the proper surface presentation of the cell adhesion domain (60). The cell binding activity of invasin and the intimins is localized within the last C-terminal amino acids.…”
mentioning
confidence: 99%
“…к этой группе аутотран-спортных белков относят инвазин энтеропатогенных бактерий Y. pseudotuberculosis и Y. enterocolitica [46]. в клетках возбудителя чумы ген inv инактивирован вставкой IS200, но присутствует его гомолог [30].…”
Section: Issueunclassified